Self-reported HPV vaccination status and HPV vaccine hesitancy in a nationally representative sample of emerging adults in Croatia - Tatjana Nemeth Blažić; Ivana Božičević; Mirjana Lana Kosanović Ličina; Aleksandar Štulhofer; Iskra Alexandra Nola (Frontiers Media S.A., 2023)
IntroductionThe aim of this study was to determine self-reported human papillomavirus (HPV) vaccination status among emerging adults in Croatia, intention to get the HPV vaccine among unvaccinated individuals and correlates of HPV vaccine hesitancy.MethodsData were collected via a cross-sectional survey based on a probabilistic national sample. The sample included 1,197 individuals aged 18-25 years (50.6% were women) who were recruited from November 2021 to February 2022 as part of the commercial online panel. Analyses included 981 participants who correctly answered two "attention trap" questions using descriptive statistics and multivariate analyses. The data were post-hoc weighted for gender and age and adjusted for clustering effect. To adjust standard errors for the sampling design, multivariate analyses were carried out using the complex samples module in the IBM SPSS 27 statistical software package.ResultsOverall, 18.3% of participants (25.0% of women and 11.7% of men) reported that they were HPV vaccinated, while 21.9% did not know their HPV vaccination status. Of those vaccinated, 65.6% were women. The odds of being HPV-vaccinated were significantly higher among female participants. Among the unvaccinated, 35.4% expressed a willingness to get the vaccine. The odds of vaccination hesitancy were significantly lower among women, participants who reported a higher perceived risk of STIs, those who recognized that HPV could result in cervical cancer, and significantly higher among those who were more religious.ConclusionOur findings suggest a need to increase HPV vaccination uptake in Croatia through raising awareness about HPV vaccine effectiveness and also through the implementation of strategies to make vaccination more available.